Regenerated Microvascular Networks in Ischemic Skeletal Muscle - Yin, Hao; Arpino, John-Michael; Lee, Jason J.; Pickering, J. Geoffrey (Frontiers in Physiology, 2021)
Skeletal muscle is the largest organ in humans. The viability and performance of this metabolically demanding organ is exquisitely dependent on the integrity of its microcirculation. The architectural and functional attributes of the skeletal muscle microvasculature are acquired during embryonic and early postnatal development. However, peripheral vascular disease in the adult can obliterate the distal microvasculature, together with damaging the skeletal myofibers. Importantly, adult skeletal muscle has the capacity to regenerate. Understanding the extent to which the microvascular network also reforms, and acquires structural and functional competence, will thus be critical to regenerative medicine efforts for those with peripheral artery disease. Herein, we discuss recent advances in studying the regenerating microvasculature in the mouse hindlimb following severe ischemic injury. We highlight new insights arising from real-time imaging of the microcirculation and computational modeling. This includes identifying otherwise hidden flaws in both network microarchitecture and function, deficiencies that could underlie the progressive nature of peripheral artery disease and its refractoriness to therapy. Recognizing and overcoming these vulnerabilities in regenerative angiogenesis will be important for advancing treatment options for peripheral artery disease.